2021
DOI: 10.3390/foods10081966
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities for Morus alba L., Focusing on the Immunostimulatory Property from the Fruit Aqueous Extract

Abstract: Depending on the extraction method, numerous compounds that have specific pharmacological effects can be obtained from M. alba L. There is a growing scientific interest in health problems related to aging. Efforts to develop safe immune-enhancing pharmaceuticals are increasing. This review aims to summarize and critically discuss the immunity enhancement effects and pharmaceutical efficacy of M. alba L. extracts. The scientific database search was conducted using Google Scholar, Web of Science, and PubMed unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…According to Bencao Gangmu (A.D.1578–1593) and Donguibogam (A.D. 1613), Morus alba L. fruit has been a traditional plant with many applications including the ability to alleviate hyperglycemia and hypertension, enhance liver and kidney function, remedy fever, strengthen the joints and moisten dryness and other disorders for thousands of years in East Asia [ 11 , 12 ]. In the Chinese pharmacopoeia version of 2020, Morus alba L. fruit is used for the treatment of liver and kidney deficiency, dizziness and tinnitus, palpitation and insomnia, premature graying hair, diabetes, constipation and intestinal dryness [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Bencao Gangmu (A.D.1578–1593) and Donguibogam (A.D. 1613), Morus alba L. fruit has been a traditional plant with many applications including the ability to alleviate hyperglycemia and hypertension, enhance liver and kidney function, remedy fever, strengthen the joints and moisten dryness and other disorders for thousands of years in East Asia [ 11 , 12 ]. In the Chinese pharmacopoeia version of 2020, Morus alba L. fruit is used for the treatment of liver and kidney deficiency, dizziness and tinnitus, palpitation and insomnia, premature graying hair, diabetes, constipation and intestinal dryness [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anticarcinogenic mechanisms of mulberry phenols demonstrated in several cell cancer lines or in animal tumor models include antioxidant activity, antiproliferation, the induction of apoptosis and antiangiogenic activity [2,[128][129][130].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Recently, it was reported that M. alba fruits induce the phenotypic maturation of dendritic cells due to the polysaccharides in the composition, and can thus be used as an adjunct in dendritic-cell cancer immunotherapy [128].…”
Section: Immunomodulatory Effectmentioning
confidence: 99%
“…The fruit of Morus alba (MA) L. (mulberry), from the family Moraceae, has been consumed as a food and dietary supplement for a long time and is rich in vitamin C, anthocyanins, flavonoids, and alkaloids. MA fruit and fruit extracts have shown antioxidant, antidiabetic, antiatherosclerotic, antiobesity, anticholesterol, and antibacterial activities, as well as immune enhancement, neuroprotective, and hepatoprotective properties (Chan et al, 2016;Chang et al, 2021;Hansawasdi and Kawabata, 2006;Zafar et al, 2013;Zhang et al, 2018). MA extracts are considered safe to use without severe side effects.…”
Section: Introductionmentioning
confidence: 99%